ANALISA YURIDIS TENTANG PUTUSAN HAKIM DALAM SENGKETA WARIS ADAT - Nanin Koeswidi Astuti (to-ra, 2016)
Inheritance is one of the most important events in human life, because every human being will experience the phase of death. At the time of the death of this person of course raises a new legal event that is the transfer of rights and responsibilities of a deceased to his heirs. Customary inheritance law based the division of inheritance based on patrilineal, matrilineal and bilateral / parental kinship systems and also based on collective inheritance systems, individual inheritance systems or major inheritance systems. Kata Kunci: Sengketa Waris Adat, Hukum Waris Adat, Harta Waris, Pewarisan